In-Vitro Evaluation of the Antibacterial Activity of the Methanol Leave Extract of Lawsonia Inermis Against Methicillin-Resistant Staphylococcus Aureus (MRSA) - Enwa Felix Oghenemaro; Jemikalajah Daniel Johnson; Oyubu L Obaro; Adjekuko Collins; Ukah Faith Erezi (Journal of Pharmaceutical Research)
This study is to determine the antibacterial efficacy of Lawsonia inermis against methicillin-resistant Staphylococcus aureus (MRSA) which has become a leading cause of infections. The leaves of Lawsonia inermis also known as Henna or lalley leave were subjected to extraction with seventy percent (70%) methanol using the cold maceration technique after which phytochemical screening and partitioning were carried out following standard procedures, hence, three fractions of the methanol extract of Lawsonia inermis (crude extract, aqueous and chloroform fractions) were used against thirty strains of MRSA by using the agar well-diffusion and minimum inhibitory concentration as a determination method. Preliminary phytochemical screening revealed the presence of Alkaloids, Saponins, Tannins, Terpnoids, and steroids. A two old serial dilution was done for each of the fractions viz; 100mg/ml, 50mg/ml, 25mg/ml, 12.5mg/ml and 6.25mg/ml. The various dilutions were used on the test organism and there was increase in zones of inhibitions with increase in extract concentrations. At 100mg/ml, the crude fraction had a maximum inhibition zone of 15.30mm which was higher than the inhibition zone of the standard antibiotic used, and a minimum inhibition zone of 9 mm as compared to the standard antibiotic used having a minimum inhibition zone of 4.33mm. Among all the fractions used, the crude fraction of the methanol extract of Lawsonia inermis showed the best activity against the test organism (MRSA) Methicilin Resistant Staphylococcus aureus. Others showed lesser activity as compared to the standard antibiotic used. Keywords: Lawsonia inermis linn, MRSA, Crude extract